Harmonized decision‐making in managing reliability and safety - Ben‐Yair, Avner; Golenko‐Ginzburg, Dimitri; Laslo, Zohar (Journal of Business Economics and Management, 2005)
A hierarchical technical system functioning under random disturbances and being subject to critical failures at the bottom level which may result in an accident or a hazardous condition including environmental safety violations at the upper level is considered. Certain primary elements at the bottom level, together with their corresponding primary failures, can be refined by undertaking technical improvement. The list of the latter is pre‐given as well. Assume that by means of simulation modeling (SM) it is possible to evaluate the increment of the system's reliability by implementing any set of technical improvements. The harmonization models center on determining an optimal sub‐set of technical improvements in order:• either to maximize the system's reliability subject to a restricted budget assigned for the improvements’ implementation, or• to minimize the system's budget subject to a reliability value restricted from below.First Published Online: 14 Oct 2010